Students’ Strategies in Understanding Reading Section of TOEFL - Rahmadani, Arvya; Dollah, Syarifuddin; Sakkir, Geminastiti (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
This study aimed to find out the students’ strategies used in the reading section of TOEFL. This research design used qualitative research with qualitative descriptive. The population of the research was English Literature students in the academic year of 2020 at Universitas Negeri Makassar. The sample was 22 students used purposive sampling to gain the data. The data was collected using a questionnaire and Interview. In this study, the researcher analyzed data using reduction, display, and draw a conclusion. Based on the research results, the researcher found that there were some strategies used by students to overcome their problems in understanding the reading section of TOEFL. The result showed students used reading the questions before reading the text, making notes or summarizing while reading the TOEFL test, preparing before the test by familiarizing with English texts, and using skimming and scanning techniques. In conclusion, the survey results regarding the Reading Section in the TOEFL test for Universitas Negeri Makassar students clearly illustrate the challenges faced and the strategies implemented.